Comparison of Three Independent Methods of Ampicillin Detection Using Hydrogen Peroxymonosulfate - S. Р. Karpova; N. Ye. Blazheyevskiy (Антибиотики и Химиотерапия, 2021)
Three unified procedures have been developed. The possibility of quantitative determination using the methods of kinetiс spectrophotometry, voltammetry, and redox titration of ampicillin (Amp) as a pure substance and in a drug using potassium hydrogen peroxomonosulfate (KHSO5) as an analytical reagent has been shown.